Relationship between Social Media Information and Attitudes Toward Avoiding AIDS and Promiscuity - Angela Librianty Thome; Nofita Dewi Kok Mesa (Indonesian Journal of Global Health Research, 2024)
Currently, there are cases of AIDS transmission due to HIV in teenagers and it has become a serious global problem. Teenagres are quite exposed to information media, making it possible for teenagers to know things related to health. So this research aims to analyze and explain wheter or not there is a relationship between exposure to social media information by teenagers and attitudes towards preventing AIDS and promiscuity. The research design used cross-sectional where samples were taken using Proportionate Stratified Random Sampling. Questionnaires for each variable were administered and tested using Spearman’s Rho Correlation. There is a relationship between exposure to social media information and attitudes towards avoiding AIDS and promiscuity with a significance value of <0.05. Exposure to information on social media turns out to be related to teenagers’ attitudes towards avoiding AIDS and promiscuity where information via social media about this matter.